Abhängigkeit der Exposition von der Zellgröße beim Mobilfunk unter Gewährleistung der Versorgung - Baldauf, Michael (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2015)
The influence of the cell size of mobile communication networks onto the exposure to electromagnetic fields is investigated in this work. The exposure is assessed by means of a radio network planning. In a novel approach the path loss for the coverage and the path loss for the exposure are distinguished. The developed model is applied to different wave propagation models and cell structures. The results are discussed.